Kiss Kiss - Dahl, Roald (London : Penguin, 2011)
What could go wrong when a wife pawns the mink coat that her lover gave her as a parting gift? What happens when the priceless piece of furniture is the subject of a deceitful bargain? Can a wronged women take revenge on her dead husband? In these dark, disturbing stories Roald Dahl explores the sinister side of human nature: the cunning, sly, selfish part of each of us that leads us into territory of unexpected and unsettling. Stylish, macabre and haunting, these takes will leave you with a delicious feeling of unease
The landlady -- William and Mary -- The way up to heaven -- Parson's pleasure -- Mrs Bixby and the colonel's coat -- Royal jelly -- Georgy Porgy -- Genesis and catastrophe -- Edward the Conqueror -- Pig -- The champion of the world
Originally published: New York: Knopf, 1959; London: Michael Joseph, 1960
Keywords: Short stories -- Fiction